ANALISIS KEBIJAKAN PENGELOLAAN AIR BAKU BERKELANJUTAN DI SUB DAS KONAWEHA KABUPATEN KONAWE SULAWESI TENGGARA - Ridwan Adi Surya; M Yanuar J. Purwanto; Asep Sapei; Widiatmaka Widiatmaka (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Decrease in water availability due to changes in land use has been occurred in Konawe, while water demand is likely to increase. In terms of the sustainability of water supply, it is quite worrying. This study aims to analyze: (1) level of sustainability, (2) important factors that affect sustainability, (3) role of institutions in the sustainable management of water resources in the Konaweha Sub Watershed. MDS analysis with Rap-Konawe results showed the status of the sustainability of water supplies in Konaweha SubWatershed is less sustainable with the sustainability index of 41,40%. Ecological dimension is sustainable enough (52,36%), economic dimension is less sustainable (36,93%), social dimension is less sustainable (34,16%), technology dimension is less sustainable (35,39%), and institutional dimension is less sustainable (35,39%). ISM analysis results showed that there are three elements that need to be considered: (1) Constraints (reduction in water absorption due to reduced function of vegetation in catchment area, and lack of coordination of water resource management among stakeholders), (2) Needs (improvement of knowledge and skills of government personnel, and increase the awareness of stakeholders), and (3) Institutions (BPDAS Sampara and Forest Service).